Biochemical and Histophysiological impact of Curcumin on Breast Cancer. A Cross Sectional Clinical Study - Naveed Shuja, Uzma Hameed, Hasan Akbar Khan, Allah Wadhayo Kalo, Urwa Sarwar, Muhammad Waqas Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Hypothesis: The active anti-carcinogenic compound of Curcuma longa a member of ginger family is curcumin which inhabit the growth of tumor in breast cancer. Aims and objectives: The aims and objectives of present study were to determine the clinical and preclinical effects of curcumin against breast cancer. Materials and Methods: 100 women patients with grade- I and grade-II breast cancer were treated with 10g/day curcumin powder orally for six months. The tumor markers such as CA 15-3, CA 27.29, Carcinoembryonic antigen (CEA) and CA 125 were measured from blood serum of each patient. Conclusion: In the present study it was concluded that a significant changes (p<0.05) come out after 6 month in blood serum levels of 10mg/day oral curcumin treated group-B and group–D as compared to group-A and group-C regarding tumor markers such as CA 15-3, CA 27.29, Carcinoembryonic antigen (CEA) and CA 125.